2014
DOI: 10.1002/glia.22742
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of monoacylglycerol lipase inhibits oligodendrocyte excitotoxicity and prevents demyelinationin vivo

Abstract: The endocannabinoids 2-araquidonoylglycerol (2-AG) and anandamide (AEA) are bioactive lipids crucially involved in the regulation of brain function in basal and pathological conditions. Blockade of endocannabinoid metabolism has emerged as a promising therapeutic strategy for inflammatory diseases of the central nervous system, including myelin disorders such as multiple sclerosis. Nevertheless, the biological actions of endocannabinoid degradation inhibitors in oligodendrocytes and white matter tracts are sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
76
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 56 publications
4
76
1
5
Order By: Relevance
“…We assume that the increased activation of microglia/monocytes and/or astrocytes in the white compared to the gray matter results in a higher lesion expansion. In support of this assumption is the observation that in the cuprizone model, explicit microgliosis is evident in regions of profound demyelination [62], that prevention of demyelination is paralleled by a reduced activation of microglia cells [63][64][65], and that the application of the microglia inhibitor minocycline [66] ameliorates demyelination in the cuprizone model [67]. Similar observations have been reported in the LPC model [68].…”
Section: Discussionsupporting
confidence: 64%
“…We assume that the increased activation of microglia/monocytes and/or astrocytes in the white compared to the gray matter results in a higher lesion expansion. In support of this assumption is the observation that in the cuprizone model, explicit microgliosis is evident in regions of profound demyelination [62], that prevention of demyelination is paralleled by a reduced activation of microglia cells [63][64][65], and that the application of the microglia inhibitor minocycline [66] ameliorates demyelination in the cuprizone model [67]. Similar observations have been reported in the LPC model [68].…”
Section: Discussionsupporting
confidence: 64%
“…In fact, the increase of 2-AG availability by inhibiting the activity of monoacylglycerol lipase with JZL-184 restored cell proliferation in the absence of mitogens present in the culture media, an effect mimicked by exogenously added 2-AG. Interestingly, a recent report showed that JZL-184 protects oligodendrocytes in vitro from excitotoxic injury mediated by activation of AMPA receptors, an effect involving the activation of CB1 receptors (Bernal-Chico et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The protocol used was modified from previously described80. Demyelination was induced by feeding 8 weeks old male C57/BL6 mice ad libitum with 0.2% cuprizone (bis-cyclo-hexanone-oxaldihydrazone; Sigma) mixed with milled chow (Altromin) for 5 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…The corpus callosum of three animals per condition was studied. For histological examination, forebrain coronal sections (20 μm) were taken of the rostral part of the corpus callosum as previously described8081 and stained with eriochrome cyanine using a standard protocol in order to study the myelin. Briefly, cryosections on glass slides were immersed in acetone for 5 minutes, dried and submerged in eriochrome cyanine solution (Sigma) for 1 hour and then differentiated in 5% (w/v) iron alum for 5–10 minutes, followed by a second differentiation with borax-ferricyanide solution for 5 minutes.…”
Section: Methodsmentioning
confidence: 99%